Predicting mergers and acquisitions : a study of Tobin's Q. - Chong, Hui Shan. (2009)
This paper attempts to document the relations between takeover probability and a comprehensive set of takeover determinants, with an emphasis on Tobin’s Q. We find firms characterized by low Q ratios are more likely to be the targets of takeovers. This study makes use of a modified methodology that takes into account industry-wide levels in Q ratios. The results indicate that the industry-adjusted Q produces a more significant and accurate measure in determining takeovers targets. Analysis has also been done to examine whether takeovers motivated by low Q ratios are due to market misvaluation or the Q-theory of investments. We find insignificant support for the Q-theory of investments which implies that management inefficiencies have limited explanatory power for the takeover sample in this study.